Stem cell-derived exosomes for ischemic stroke: a conventional and network meta-analysis based on animal models - Xu, Kangli; Zhao, Xiaohui; He, Yuxuan; Guo, Hongxin; Zhang, Yunke (Frontiers in Pharmacology, 2024)
Objective We aimed to evaluate the efficacy of stem cell-derived exosomes for treating ischemic stroke and to screen for the optimal administration strategy.We searched PubMed, Web of Science, Embase, Cochrane Library, and Scopus databases for relevant studies published from their inception to December 31, 2023. Conventional and network meta-analyses of the routes of administration, types, and immune compatibility of stem cell-derived exosomes were performed using the cerebral infarct volume(%) and modified neurological severity score (mNSS) as outcome indicators.Results A total of 38 randomized controlled animal experiments were included. Conventional metaanalysis showed that compared with the negative control group: intravenous administration significantly reduced the cerebral infarct volume(%) and mNSS; intranasal administration significantly reduced the cerebral infarct volume(%); and intracerebral administration significantly reduced the mNSS. ADSC-Exos, BMSC-Exos, DPSC-Exos and NSC-Exos significantly reduced the cerebral infarct volume(%) and mNSS; EPC-Exos, ESC-Exos, iPSC-Exos and NPC-Exos significantly reduced the cerebral infarct volume(%); UCMSC-Exos significantly reduced the mNSS; and there was no significant difference between USC-Exos and negative controls. Engineered modified exosomes had better efficacy than unmodified exosomes. Both allogeneic and xenogeneic stem cell-derived exosomes significantly reduced the cerebral infarct volume(%) and the mNSS. The network meta-analysis showed that intravenous administration was the best route of administration for reducing the cerebral infarct volume(%) and mNSS. Among the 10 types of stem cell-derived exosomes that were administered intravenously, BMSC-Exos were the best type for reducing the cerebral infarct volume (%) and the mNSS. Allogeneic exosomes had the best efficacy in reducing the cerebral infarct volume (%), whereas xenogeneic stem cell-derived exosomes had the best efficacy in reducing the mNSS.This meta-analysis, by integrating the available evidence, revealed that intravenous administration is the best route of administration, that BMSC-Exos are the best exosome type, that allogeneic exosomes have the best efficacy in reducing the cerebral infarct volume (%), and that xenogeneic exosomes have the best efficacy in reducing mNSS, which can provide options for preclinical studies. In the future, more high-quality randomized controlled animal experiments, especially direct comparative evidence, are needed to determine the optimal administration strategy for stem cell-derived exosomes for ischemic stroke.